2004
DOI: 10.1128/iai.72.9.5168-5174.2004
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Gene Expression in Toll-Like Receptor-Competent and -Deficient Mice Infected with Leishmania major

Abstract: We studied the expression of a subset of chemokines, including RANTES/CCL5, MIP-1␣/CCL3, IP-10/ CXCL10, and MCP-1/CCL2, in Toll-like receptor (TLR)-competent and -deficient mice after infection with Leishmania major. Chemokine expression at the site of infection (the footpad), in the draining lymph nodes and in the spleens of infected animals was determined by using two different methods of analysis. The results indicate that L. major infection causes overall upregulation of RANTES/CCL5, MIP-1␣/CCL3, IP-10/CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
(55 reference statements)
3
29
0
7
Order By: Relevance
“…Nevertheless, further studies showed that TLR4 was less important than TLR2 and cytokine expression was independent of this receptor 2 . KAVOOSI et al demonstrated in two studies that TLR4 is not activated by Leishmania 10,11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, further studies showed that TLR4 was less important than TLR2 and cytokine expression was independent of this receptor 2 . KAVOOSI et al demonstrated in two studies that TLR4 is not activated by Leishmania 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, discrepancy in TLR signaling has been observed when in vitro and in vivo studies have been published 2,[10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies using mouse L. major model have shown that the draining lymph nodes from diseaseresistant C3H and C57BL/6 mice contain significantly higher amounts of MCP-1, IP-10, and lymphotactin mRNA than those from susceptible BALB/c mice [38,40]. L. major-infected C57BL/6 mice also display increased levels of CXCL10 in their lesions [42]. On the other hand, C57BL/6 mice lacking the MCP-1 receptor CCR2 show decreased migration of Th1-inducing dendritic cells from the site of infection to the lymph nodes, mount a Th2 response, and develop non-healing lesions [38].…”
mentioning
confidence: 99%
“…Case of ISPs interfering in trypsin-like action of sand fly midguts has been reported [25]. Moreover, a few parasites of Leishmania family also have mechanisms that intensify their resistance to proteolytic attack without inhibiting the overall proteolytic activity in the midgut [28].…”
Section: Alternative Pathogenicity Of Parasitesmentioning
confidence: 99%
“…In this diagnostic method, promastigotes of L. donovani are grown to log phase and lysed and the soluble protein is used as sample [18]. With Western blotting, one can find even minor antigenic differences among various organisms and thus detect cross-reactive antigens [28]. Though, the process is time consuming, technically cumbersome, and expensive [8] tonsils, and skin; and even as widely disseminated disease [4,8].…”
Section: Western Blotmentioning
confidence: 99%